2021
DOI: 10.3390/ma14133687
|View full text |Cite
|
Sign up to set email alerts
|

On Developing a Hydrophobic Rubberized Cement Paste

Abstract: It is well known that most cement matrix materials are hydrophilic. For structural materials, hydrophilicity is harmful because the absorption of water will induce serious damage to these materials. In this study, crumb rubber was pretreated by partial oxidation and used as an additive to develop a hydrophobic rubberized cement paste. The pretreated crumb rubber was investigated using Fourier-transform infrared spectrometry (FT-IR) to understand the function groups on its surface. The pyrolysis oil adsorbed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The high porosity is probably balanced by a non-absorbing repellent character, which partially reduced the effect of high porous inner structure. From the point of view of moderation of water ingress, the most advantageous hygric parameters were measured for the samples containing crumb rubber, which was due to its hydrophobic nature recently reported by Chen et al [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high porosity is probably balanced by a non-absorbing repellent character, which partially reduced the effect of high porous inner structure. From the point of view of moderation of water ingress, the most advantageous hygric parameters were measured for the samples containing crumb rubber, which was due to its hydrophobic nature recently reported by Chen et al [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increasing industrial waste generation on a global scale means there is a growing interest in using waste materials as additives for cement and construction applications. Industrial wastes, including paper sludge ash, rubber, and short textile waste fibers, have been the subject of investigation in this context (Wong et al, 2015;Chen et al, 2021;Sadrolodabaee et al, 2021).…”
Section: Research Articlementioning
confidence: 99%
“…Their findings indicated that replacing 12% of Portland cement with paper sludge ash led to an 84% reduction in water absorption without negatively impacting material strength. Another investigation by Chen et al (2021) explored the use of crumb rubber treated with partial oxidation as an additive in cement paste. The study revealed that pretreated crumb rubber facilitated the development of a hydrophobic rubberized cement paste.…”
Section: Research Articlementioning
confidence: 99%
“…Treating rubber powder with a silane coupling agent and carboxylated styrene butadiene rubber latex improved compressive strength and flexural strength by 4% and 13%, respectively, compared to the control concrete without rubber [33]. The partial oxidation treatment produced hydrophilic functional groups on rubber surfaces leading to the higher compressive strength of rubberised concrete compared to control samples without rubber powder [34,35]. A further study demonstrated that rubber powder oxidised with KMnO 4 solution and then sulphonated with NaHSO 3 achieved a 41.1% increase in the adhesion strength of the rubber and OPC paste [36].…”
Section: Introductionmentioning
confidence: 97%